Festifavelisation: mega-events, slums and strategic city-staging – the example of Rio de Janeiro - Steinbrink, Malte (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Mega-events are increasingly often taking place in countries of the Global South. In the socio-spatially deeply fragmented host cities these spectacles encompass extremely transformative urban processes. This paper will consider the festivalisation of Rio de Janeiro in the preparatory phase of the 2014 FIFA World Cup and the 2016 Summer Olympics. It focuses on the urban policy in relation to how Rio deals with its favelas. The aim of the article is to critically assess current measures of ‘invisibilisation’, ‘pacification’, ‘beautification’ and ‘touristic staging’ of favelas against the backdrop of the upcoming events.